Review: The Biochemistry of Love and Loving - Onyinyechi, Nwachukwu Favour; Joseph, Ikwebe; Umaru, Kerenhappuch Isaac; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
Human love is more complex than simple feedback mechanisms. Love create its own reality. The biology of love originates in primitive parts of the brain; the emotional core the human nervous system, that evolved long before the cerebral cortex. The brain of human ‘in love’ is flooded with sensations, often transmitted by the vagus nerve, creating much of what we experience as emotion. The modern cortex struggles to interpret the primal messages of love, and weaves a narrative around incoming visceral experiences, potentially reacting to that narrative rather than reality. The four functions of love include; Romantic love (erotic) love, Friendly love or Platonic love (Philia), Familial love (Storge) and Unconditional love (Agape). Glutamate is an excitatory neurotransmitter released by the nerve cell. It’s mostly referred to as the master switch of the brain. Lust: Characterized by a strong desire for sexual gratification and is primarily driven by testosterone and oestrogen. Attraction: This stage involves intense romantic and sexual feelings, associated with dopamine, norepinephrine, and serotonin. Attachment: The final stage, involving long-term commitment and bonding, is influenced by oxytocin and vasopressin. The hypothalamus of the brain plays a big role in stimulating the production of sex hormones testosterones and oestrogen from the testes and ovaries. These chemicals are often stereotyped as being ‘male’ and ‘female’ respectively, both plays a role in men and women. Males produce forty to sixty times more of the testosterones. Testosterones increases the libido in male and female. The effect is less pronounced with oestrogen, but some woman report being more sexually motivated around the time the ovulate, when oestrogen levels are highest. Conclusions: Love is a complex neurobiological phenomenon, relying on trust and belief as well as brain reward activity.